Let’s tasmik mobile apps : Quran tasmik application using deep learning - Nor Nabilah, Mustapha; Syamimi Mardiah, Shaharum; Ahmad Afif, Mohd Faudzi (2021)
Let’s Tasmik allow users to record their voice and the system will recognize the spoken verse and detect the mistake. Let’s Tasmik may replace current traditional memorization method, which is conventional method.